2020
DOI: 10.36965/ojakm.2020.8(1)32-52
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing information, acquiring knowledge, and making decisions regarding web accessibility

Abstract: We address the disparity between availability of information and its actual implementation in decisions in the context of Web Accessibility (W-A). Organizations are aware of the importance of W-A for alleviating barriers to interaction with online platforms, such as visual, motor, hearing, and cognitive impairments. Information regarding inclusion design is abundant but implementation is partial. Applying W-A refers to implementing technical and graphical solutions to assist people with disabilities in access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Changes in industrial leadership from an incumbent to a latecomer are often observed in several industries [17]. Latecomers create opportunities for R&D cooperation with forerunners to improve the efficiency of technology catch-up [18].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in industrial leadership from an incumbent to a latecomer are often observed in several industries [17]. Latecomers create opportunities for R&D cooperation with forerunners to improve the efficiency of technology catch-up [18].…”
Section: Introductionmentioning
confidence: 99%